"Lives full of struggle and triumph" : Southern women, their institutions, and their communities - Clayton, Bruce; Salmond, John A. (New perspectives on the history of the South., 2003)
''A splendid sampler of the very latest and best of scholarship in the field of southern women's history.''--Thomas Appleton, Eastern Kentucky UniversitySpanning the sweep of southern women's history from colonial times to the late 20th century, this collection represents the best scholarship on the lives and experiences of black and white southern women.